Accumulation of Indole‐3‐Acetic Acid in Rice sl Mutant Leaves Infected with Bipolaris oryzae. Issue 7 (4th March 2016) - Ishihara, Atsushi; Fukami, Arisa; Matsuda, Yoko; Nakajima, Hiromitsu; Miyagawa, Hisashi
Abstract: Rice leaves accumulate serotonin in response to infection by Bipolaris oryzae . The leaves of the sl mutant, which is deficient in the gene encoding tryptamine 5‐hydroxylase, accumulate tryptamine instead of serotonin upon infection by B. oryzae . Because tryptamine is a possible precursor of indole‐3‐acetic acid (IAA), we investigated the accumulation of IAA in sl leaves infected with B. oryzae . Liquid chromatography coupled with tandem mass spectrometry analysis indicated that IAA accumulated at approximately 1.5 μ mol/gFW in the leaves of sl mutant. This accumulation was suppressed by 95% by the treatment with the tryptamine decarboxylase inhibitor, ( S) ‐α‐(fluoromethyl)tryptophan, at 100 μ m, indicating that tryptamine served as the precursor of IAA. The accumulation of IAA was not reproduced by treatment with CuCl2 or by exogenous feeding of tryptamine. Furthermore, inoculation of Magnaporthe grisea induced only a lower level of IAA accumulation. On the other hand, B. oryzae produced IAA in culture media containing tryptamine. These findings strongly suggested that the metabolism of tryptamine by B. oryzae was responsible for IAA accumulation in the leaves of the sl mutant. Serotonin added to the culture media was also converted into 5‐hydroxyindole‐3‐acetic acid (5HIAA) at a rate similar to that of tryptamine. Considering that wild‐type rice leaves accumulate serotonin for defensive purposes, reducing the concentration of serotonin by conversion into 5HIAA may be significant as a detoxification process in the interaction between B. oryzae and rice.